# How Do I Solve 4x+3(2-X)=8-2x?

This is an easy algebraic problem. All you need to do is to follow the steps below.
4x + 3(2 - x) = 8 - 2x
4x + 6 - 3x = 8 - 2x
x - 6 = 8 - 2x
3x = 14
thanked the writer.
To solve this problem you need to look at the left side of the equation distribute +3(2x) by multiplying 3 and 2 then 3 and negative x to get rid of the parenthesis.once you've done thta then it will look like this:
4x+6-3x=8-2x. Next combine like terms on the left side (4x-3x) then the problem will look like this: X+6=8-2x then you need to get rid of one of the x's. Add 2x on the right side to get rid of the x and do the same to the x on the left.now the problem looks like this: 3x+6=8.now you must get rid of the #s. Now subtract 6 from both sides.your problem should look like this now:3x=2. Then divide 3 by both sides of the equation. And the answer is x=0.7.
thanked the writer.
14/3
thanked the writer.
4x + 6 - 3x = 8 - 2x

4x - 3x + 2x = 8 - 6

3x = 2

3x/ 3 = 2/3

x = 0.6666 (recuring)
thanked the writer. 